Tradisi Beuma dan Pandangan akan Alam Dayak Suaid sebagai Pelestarian Lingkungan - Kristianus damianus apo (Universitas Tanjungpura, 2022)
The Dayak community in Sejiram Village, Seberuang District, Kapuas Hulu Regency have their tradition of Beuma and Menugal. The tradition of Beuma and Menugal has been carried out from the time of the ancestors, right through up until the present. This tradition, which aims to preserve nature, is carried out by the Suaid Dayak community, by utilizing their existing local knowledge. This study aims to describe and analyse these traditions, with their stages, their meanings and their customs of forest conservation. The researcher used a phenomenological analysis methodology according to Valentinus Saeng's thoughts, as seen in Valentinus’s presentation about the wisdom of the Mualang Dayak tribe. The researcher saw how the Dayak people cared for the jungle and rivers, and so he take took these observations and applied them to forest conservation. Then the study was based on my personal experience as a native of West Kalimantan. The study used qualitative and descriptive-analytic research methods. The data collection techniques used were interview, participation observation, and documentation. The study focuses on the Suaid Dayak community at the Sejiram Village, the Seberuang District, the Kapuas Hulu Regency, and how they were in conserving forests through the Beuma and Menugal traditions. The findings in of this study were that the Suaid Dayak people in West Kalimantan upheld their customs of forest conservation, as well as their togetherness and brotherhood qualities. Farming is the root and source of life for the Suaid Dayak people. As conclusion, the Beuma and Nugal traditions in the Suaid Dayak community are strongly rooted into their local wisdom.